VESTIBULAR VERTIGO - M. V. Zamergrad (Неврология, нейропсихиатрия, психосоматика, 2009)
The authors consider the cardinal causes of vestibular vertigo, a benign paroxysmal positional vertigo, Meniere's disease, vestibular neuroni-tis, vestibular migraine, cerebrovascular diseases. It gives brief data on the etiology, pathogenesis, clinical manifestations, and treatment of these diseases. The diagnosis of the latter is largely based on a patientKhs complaints and medical history data and frequently requires no additional instrumental study. The currently available treatments for various diseases manifesting as vestibular vertigo are analyzed. Vestibular exercises and rehabilitation maneuvers that are effective in benign positional vertigo are noted to play an important role. In addition, methods for drug stimulation of vestibular compensation in central and peripheral vestibulopathies are described.